2019
DOI: 10.31590/ejosat.539318
|View full text |Cite
|
Sign up to set email alerts
|

A Review Study on the Using of Diethyl Ether in Diesel Engines: Effects on HC Emissions

Abstract: This study was compiled from the results of various researches performed on using diethyl ether as a fuel or fuel additive in diesel engines. Three different methods have been used the reduction of the harmful exhaust emissions of diesel engines. The first technique for the reduction of harmful emissions has improved the combustion by modification of engine design and fuel injection system, but this process is expensive and time-consuming. The second technique is the using various exhaust gas devices like cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Diethyl ether was added as an additive in EKB20 as it is a highly volatile, ammable, colourless liquid with a distinctive odour. It has a high cetane number, making it a suitable fuel for CI engines reducing combustion time (Sezer 2019). Only 5% and 10% of diethyl ether on a volume basis are added in order to limit the combustion characteristics of EB20 (Prakash et al 2011).…”
Section: Preparation Of Karanja Bio-oil -Diesel Fuel Emulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diethyl ether was added as an additive in EKB20 as it is a highly volatile, ammable, colourless liquid with a distinctive odour. It has a high cetane number, making it a suitable fuel for CI engines reducing combustion time (Sezer 2019). Only 5% and 10% of diethyl ether on a volume basis are added in order to limit the combustion characteristics of EB20 (Prakash et al 2011).…”
Section: Preparation Of Karanja Bio-oil -Diesel Fuel Emulsionmentioning
confidence: 99%
“…At the rated power output, the addition of 5% and 10% DEE resulted in the reduction of speci c fuel consumption by 16% and 18% respectively compared to EKB20. The addition of diethyl ether reduces the viscosity of EB0 and results in an improvement in fuel atomization leading to proper mixing with air and improvement in combustion (Sezer 2019). Also, the higher cetane number of DEE leads to earlier fuel combustion and complete combustion.…”
Section: Speci C Fuel Consumptionmentioning
confidence: 99%
“…Besides, popular ethers such as DEE and DME with low viscosity can overcome the high viscosity of biodiesel fuel to improve fuel injection quality. Recent studies have revealed that the addition of ether additives can improve important fuel properties, leading to improved combustion quality, brake thermal efficiency (BTE), brake specific fuel consumption (BSFC) and cylinder pressure (Sezer, 2019). More interestingly, blended fuels with the addition of these organic additives have provided environmental benefits by reducing emissions of PM, HCs, CO and NOx (Nižetić et al, 2021c)(Morales Bayetero et al, 2021.…”
Section: Introductionmentioning
confidence: 99%